Task assignment and sequencing decision model under uncertain available time of service providers. Issue 12 (2nd December 2018) - Zhen, Lu; Hao, Hao; Shi, Xin; Huang, Lufei; Hu, Yi
Abstract: This paper studies an integrated decision problem on assigning and sequencing tasks to service providers. By considering the uncertain available time of the service providers, a stochastic programming model is proposed on the basis of a finite set of scenarios. Some realistic factors are also taken into account and formulated as some non-linear cost functions, which are linearised in this study. Moreover, a heuristic solution method is designed for solving some extremely large-scale problem cases within a reasonable period of time. Numerical experiments are performed to validate the effectiveness of the proposed model and the efficiency of the proposed solution method.